1999
DOI: 10.1007/s004649901135
|View full text |Cite
|
Sign up to set email alerts
|

Incisional hernias after laparoscopic vs open cholecystectomy

Abstract: The laparoscopic technique showed a lower (although not significantly) incidence of incisional hernias than the open procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 15 publications
1
95
0
3
Order By: Relevance
“…It may be expected that incidence rate of port site hernia will increase as larger laparoscopic cannulae are used [7] . Incidence of Port Site Hernia (PSH) can be reduced by avoiding unnecessary port site extension and use of nonabsorbable sutures for closure of fascial defects larger than 10 mm [8] . It has been suggested that when the pneumoperitoneum is expelled before the extraction of the port cannulae, the pressure gradient between the intraperitoneal gas and the atmosphere allows small bowel or omentum to become attached to the end of the cannula whose subsequent withdrawal may results in a hernia [9] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be expected that incidence rate of port site hernia will increase as larger laparoscopic cannulae are used [7] . Incidence of Port Site Hernia (PSH) can be reduced by avoiding unnecessary port site extension and use of nonabsorbable sutures for closure of fascial defects larger than 10 mm [8] . It has been suggested that when the pneumoperitoneum is expelled before the extraction of the port cannulae, the pressure gradient between the intraperitoneal gas and the atmosphere allows small bowel or omentum to become attached to the end of the cannula whose subsequent withdrawal may results in a hernia [9] .…”
Section: Discussionmentioning
confidence: 99%
“…PSH is defined as an incisional hernia which occurs after minimally invasive surgery in the trocar incision site [2] . PSH occurs usually in the umbilical port site [3] . There is no early superficial bulge at the port site, so the diagnosis may not be early apparent.…”
Section: Introductionmentioning
confidence: 99%
“…The laparoscopic approach minimizes the surgical wound and reduces the risk of hernias through the use of small-caliber trocars [5]. The most common region for a trocar site hernia is near the umbilicus, usually with a larger-sized pore to facilitate the specimen removal [1,6].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of Richter's hernia was about 47.50% in early onset hernias in one series and they typically present with nausea, vomiting, pain and abdominal distention [2]. Computed tomography and gastrointestinal contrast studies have been used to aid the diagnosis of trocar site hernias [4]. The management of most of these hernias include an explorative laparotomy, widening of the trocar site, reduction of the hernia and further surgeries based on the bowel viability.…”
Section: Discussionmentioning
confidence: 99%